Extract of Solidago chilensis Meyen inflorescences: cytotoxicity and inhibitory activity on nitric oxide synthesis in activated macrophage cell line J774A.1 - Thais Morais de Brito; Fabio Coelho Amendoeira; Temistocles Barroso de Oliveira; Valber da Silva Frutuoso; Fausto Klabund Ferraris; Simone Sacramento Valverde (Universidade de São Paulo, 2020)
Solidago chilensis Meyen (= Solidago microglossa) popularly known as "Brazilian arnica" is used to treat of inflammatory disorders. S. chilensis is constant in the Therapeutic Memento of the Rio de Janeiro city and belongs to the medicinal species of Brazilian National List of Medicinal Plants of Interest of the Unified National Health System (SUS). There are no studies in the literature showing the direct activity of this plant species on immune system cells. The present study evaluated the chemical composition as well as the cytotoxic and pharmacological activity of the ether-ethanol extract from S. chilensis inflorescences (SCIE) in murine macrophage cell line J774A.1. The results showed that higher concentrations (50 to 200 µg/mL) of SCIE had significant cytotoxicity on J774A.1 cells, however, lower concentrations (from 10 to 0.1 µg/mL) did not produce significant cytotoxic effects and exhibited an inhibitory effect on nitric oxide production in LPS-stimulated J774A.1 cell line. The chemical analysis by HPLC-UV-PDA indicated that the SCIE contains flavonoid derived from quercetin and kaempferol; and diterpenes, probably labdanes. These findings complement data in the literature regarding the activity of this plant species on an important cell from the immune system involved in the innate and acquired immune response, the macrophages.